2018
DOI: 10.3171/2017.5.spine161286
|View full text |Cite
|
Sign up to set email alerts
|

Posterior inferior cerebellar artery with an extradural origin from the V3 segment: higher incidence on the nondominant vertebral artery

Abstract: OBJECTIVEThe posterior inferior cerebellar artery (PICA) and the vertebral artery (VA) often exhibit anatomical variations at the craniovertebral junction (CVJ). An example of this is the PICA originating extradurally from the V3 segment of the VA. To date, some cadaveric investigations have been reported, but the incidence and relationship of this variation to the VA and the atlas as observed on clinical imaging have not been discussed. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…An extradural origin PICA from the VA is not rare. The frequency of an extradural origin of the PICA ranges from 0.4% to 20.8% 1 , 4 , 12 , 18 , 19 , 22 - 25 . The extradurally located PICAs are exposed to injury during posterior approaches to the lower brainstem and upper cervical spine.…”
Section: Introductionmentioning
confidence: 99%
“…An extradural origin PICA from the VA is not rare. The frequency of an extradural origin of the PICA ranges from 0.4% to 20.8% 1 , 4 , 12 , 18 , 19 , 22 - 25 . The extradurally located PICAs are exposed to injury during posterior approaches to the lower brainstem and upper cervical spine.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the different reference populations, the prevalence of the arcuate foramen is highly variable (Table 1). A study from Japan analyzed 153 CTA images and showed a prevalence of 12.0% 8 . Four studies that focused on Korean individuals demonstrated a prevalence of 7.1%–26.0% in the CT scan group and 6.96%–14.0% in the X‐ray group, and the arcuate foramen was more prominent on the left side and in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…It typically arises from the intradural vertebral artery but can have an extradural origin as well occurring 5 to 18% of the time. 12 The PICA is divided into four segments, which are the anterior medullary segment, lateral medullary segment, posterior medullary (tonsillar loop) segment, and supratonsillar (cortical) segment. The anterior and lateral medullary segments provide supply to the medulla and the more distal segment branches provide supply to the posterior inferior cerebellum.…”
Section: Vertebrobasilar Systemmentioning
confidence: 99%
“…Of note, the vertebral artery can terminate in PICA approximately 0.2% of the time. 12 In addition, there can be a shared anterior inferior cerebellar artery (AICA)-PICA trunk which is common variant.…”
Section: Vertebrobasilar Systemmentioning
confidence: 99%